Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era - Wolfgang Kersten; Carlos Jahn; Thorsten Blecker; Christian M. Ringle (epubli GmbH, 2022)
This volume contains research contributions by an international group of authors addressing innovative and technology-based approaches for logistics and supply chain management. They present opportunities for enhancing resilience and sustainability as well as recent approaches for supply chain analytics and risk management. This volume, edited by Wolfgang Kersten, Carlos Jahn, Thorsten Blecker and Christian Ringle, provides valuable insights into resilience and sustainability in logistics and supply chain management with regard to: ▪ Innovation and TechnologyManagement ▪ Artificial Intelligence and Blockchain ▪ City Logistics ▪ Maritime Logistics ▪ Supply Chain Risk and Security Management
urn:nbn:de:gbv:830-882.0200445; https://econpapers.repec.org/RePEc:zbw:hiclch:267180; https://econpapers.repec.org/RePEc:zbw:hiclch:267181; https://econpapers.repec.org/RePEc:zbw:hiclch:267182; https://econpapers.repec.org/RePEc:zbw:hiclch:267183; https://econpapers.repec.org/RePEc:zbw:hiclch:267184; https://econpapers.repec.org/RePEc:zbw:hiclch:267185; https://econpapers.repec.org/RePEc:zbw:hiclch:267186; https://econpapers.repec.org/RePEc:zbw:hiclch:267187; https://econpapers.repec.org/RePEc:zbw:hiclch:267188; https://econpapers.repec.org/RePEc:zbw:hiclch:267189; https://econpapers.repec.org/RePEc:zbw:hiclch:267190; https://econpapers.repec.org/RePEc:zbw:hiclch:267191; https://econpapers.repec.org/RePEc:zbw:hiclch:267192; https://econpapers.repec.org/RePEc:zbw:hiclch:267193; https://econpapers.repec.org/RePEc:zbw:hiclch:267194; https://econpapers.repec.org/RePEc:zbw:hiclch:267195; https://econpapers.repec.org/RePEc:zbw:hiclch:267196; https://econpapers.repec.org/RePEc:zbw:hiclch:267197; https://econpapers.repec.org/RePEc:zbw:hiclch:267198; https://econpapers.repec.org/RePEc:zbw:hiclch:267199; https://econpapers.repec.org/RePEc:zbw:hiclch:267200; https://econpapers.repec.org/RePEc:zbw:hiclch:267201; https://econpapers.repec.org/RePEc:zbw:hiclch:267202; https://econpapers.repec.org/RePEc:zbw:hiclch:267203; https://econpapers.repec.org/RePEc:zbw:hiclch:267204; https://econpapers.repec.org/RePEc:zbw:hiclch:267205; https://econpapers.repec.org/RePEc:zbw:hiclch:267206; https://econpapers.repec.org/RePEc:zbw:hiclch:267207; https://econpapers.repec.org/RePEc:zbw:hiclch:267208; https://econpapers.repec.org/RePEc:zbw:hiclch:267209
Keywords: 650; Advanced Manufacturing; Industry 4.0; Artificial Intelligence; Blockchain; Innovation Management; Technology Management; Supply Chain Risk Management; Security Management; Maritime Logistics; Port Logistics; City Logistics; Sustainability